Genomic and Genotypic Characterization of Cylindrospermopsis raciborskii: Toward an Intraspecific Phylogenetic Evaluation by Comparative Genomics (vol 9, 306, 2018) - Abreu, Vinicius A. C. (2018)
Univ Sao Paulo, Ctr Nucl Energy Agr, Piracicaba, Brazil